Integrative Study of Traditional Medicinal Flora in Jorhat West - Boruah, Akash Jyoti; Boruah, Akash Jyoti; Agarwal, Khusboo (International Journal of Scientific Research in Biological Sciences, 2024)
The project examines the various use of these traditional medicinal plants in different fields and societies. For centuries, these plants have been used in traditional medicine, which is strongly influenced by cultural heritage, to heal various illnesses. These plants are essential for the primary healthcare systems in several parts of the world, particularly in countries such as India, Africa, and China. The research emphasizes how ethnobotany combines traditional knowledge with modern science, demonstrating its interdisciplinary nature and providing understanding on the creation of innovative pharmaceuticals. Furthermore, it explores the cultural importance and conservation of indigenous herbal remedies, stressing the need to uphold this ancestral knowledge for upcoming generations. For centuries, medicinal plants from traditional sources have been essential in healthcare for various cultures, serving as both remedies and key elements of cultural identity. These plants play a crucial role in the customs of native medicinal traditions such as Ayurveda, traditional Chinese medicine, and African traditional medicine. Preserving and documenting this knowledge is crucial, as it helps with biodiversity conservation and protecting cultural heritage.